Analisis Gaya Bahasa pada Puisi “Dalam Diriku” Karya Sapardi Djoko Darmono - Thesa Angesti; Rochmat Tri Sudrajat; Mimin Sahmini (Departement of Mathematics Education, 2021)
The title of this research is the analysis of figurative language in the poem “Dalam Diriku” by Sapardi Djoko Darmono. This research is a form of appreciation for literary works, especially poetry in the context of developing Indonesian language and literature. This study aims to describe and interpret the use of language style in the poem entitled “Dalam Diriku” by Sapardi Djoko Darmono. This study used descriptive qualitative method. The technique for collecting data in this study used content analysis in the poem. This research explains phenomena throught the process of observing cases or phenomena, then being interpreted, interpreted, and then formulating conclusions. The use of language style is a component that often exists in works of fiction and non-fiction in Indonesian. The results of this study show that the poem “Dalam Diriku” contains repetition, metaphor, personification, paradox to hyperbole language styles. The use of language style in the poem needs to be known as the beauty of the effect in a story so that it seems lively and interesting so that the message contained in it is easier to understand.